Precisão da técnica de absorciometria de raios-x de dupla energia na determinação da composição corporal em gatos - Borges, N. C.; Vasconcellos, Ricardo Souza [UNESP]; Canola, Julio Carlos [UNESP]; Paula, F. J. A.; Carciofi, Aulus Cavalieri [UNESP]; Pereira, Gener Tadeu [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2008)
A short-term precision error of the individual subject and the DEXA technique, such as the effect of the repositioning of the cat on the examination table, were established. Four neutered adult cats (BW=4342g) and three females (BW=3459g) were submitted to five repeated scans with and without repositioning between them. Precision was estimated from the mean of the five measurements and expressed by the individual coefficient of variation (CV). The precision error of the technique was estimated by the variance of scan pool (n=35) and expressed in CV for the technique (CVt). The degrees of freedom and confidence intervals were determined to avoid underestimation of precision errors. Bone mineral content (BMC), lean mass (LM), and fat mass (FM) averages were higher (P<0.05) when animals were repositioned. The CVt was significantly higher (P<0.05) for bone mineral density (BMD), LM, and FM when the animals were repositioned. For short-term precision measurements, the repositioning of the animal was important to establish the precision of the technique. The dual energy x-ray absorptiometry method provided precision for body composition measurements in adult cats.
Precision of dual energy x-ray absorptiometry for body composition measurements in cats
Keywords: Cat; repeatability; DEXA